Pengembangan Usaha melalui Modal Ventura: Solusi Alternatif dalam Perspektif Islam - Rasimin Rasimin (IAIN Salatiga, 2010)
Capital venture was a financing that involved high risk to establish a newbusiness for extension or refinancing without obligatory collateral. Capitalventure was a kind of additional capital from investors managed by a stateenterprise or a private enterprise. The capital was distributed to small businessor middle business which is looking for capital to increase the effort. Thedistribution of capital was based on sincerity and mutual assistance. So,investors and the institution of venture did not receive the profit from theirbusiness partners. In classical Islamic contract law (fiqh muamalah), theterm of capital venture has not been discussed yet, because it was acontemporary economic problem appeared by economist. Thus, it wasnecessary to conduct a study to know the view of Islamic law about thecapital venture, particularly about the practice of capital venture and thesystem of profit sharing. From this research, it was hoped that capital venturecould be a means of developing for the Moslem’s economics